Rowing performance after dehydration: An unexpected effect of method - Kelly, D. J.; Nepotiuk, A.; Brown, L. E. (SportRxiv Preprints, 2020)
Purpose: To investigate whether mild dehydration, as a weight reduction strategy for lightweight rowers, compromises rowing performance despite a two-hour rehydration window. Both 2000m time trial and visuomotor performance were assessed for impairment. Methods: Experienced rowers (N=14) twice performed a 2000 m rowing ergometer time trial and visuomotor battery: once euhydrated and once after mild dehydration (-1.68 ± .23% body mass reduction). Weight loss was achieved through a combination of 12-hour (overnight) fluid restriction and sauna exposure. Results: Participants were significantly slower on the 2000 m rowing trial in the dehydration condition than in the euhydration condition (2.44 ± 4.5 s, p<0.05). Hierarchical linear regression analyses revealed that these rowing performance decrements were better accounted for by dehydration achieved overnight through fluid restriction (r2=.504, p<0.01) than by dehydration achieved in the sauna (r2=.025, n.s.). Hierarchical regression also revealed a relationship between dehydration-related rowing performance decrements and dehydration-related changes in visuomotor function (r2=.310, p<0.01). Conclusions: These findings suggest that rowing time-trial performance is negatively affected by relatively small changes in hydration status (<2% body-mass dehydration) and that the method by which dehydration is achieved is important. Performance losses were associated with prolonged fluid abstinence and not with short-term thermal exposure.